2015
DOI: 10.1007/s00122-015-2547-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of co-dominant SCAR markers linked to resistant gene against the Fusarium oxysporum f. sp. radicis-lycopersici

Abstract: We developed highly reliable co-dominant SCAR markers linked to the Frl gene. FORL testing is difficult. The marker is expected to be quickly adapted for MAS by tomato breeders. Fusarium oxysporum f. sp. radicis-lycopersici causes Fusarium crown and root rot (FCR), an economically important soil-borne disease of tomato. The resistance against FCR is conferred by a single dominant gene (Frl) located on chromosome 9. The aim of this study was to develop molecular markers linked to the Frl gene for use in marker-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…In this study, we confirmed that resistance to FORL was conferred by a single dominant gene that was located on Chr. 9, as reported earlier (Vakalounakis et al 1997, Fazio et al 1999, Mutlu et al 2015, indicating that the FORL resistance in 'AV107-4' might have originated from the Frl of an S. peruvianum accession. However, the results on the genomic location of Frl were contradictory between recently published D r a f t studies and our study: by using an F 2 population, Staniaszek et al (2014) mapped the COSII marker C2_At2g38025 at 3 cM distal to Frl in line '3070'.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this study, we confirmed that resistance to FORL was conferred by a single dominant gene that was located on Chr. 9, as reported earlier (Vakalounakis et al 1997, Fazio et al 1999, Mutlu et al 2015, indicating that the FORL resistance in 'AV107-4' might have originated from the Frl of an S. peruvianum accession. However, the results on the genomic location of Frl were contradictory between recently published D r a f t studies and our study: by using an F 2 population, Staniaszek et al (2014) mapped the COSII marker C2_At2g38025 at 3 cM distal to Frl in line '3070'.…”
Section: Discussionsupporting
confidence: 71%
“…9 on Tomato-EXPEN 2000 map. Most recently, Mutlu et al (2015) reported two COSII markers that were flanking Frl by using F 2 and BC 1 populations. One of the COSII markers C2_At3g63200 was linked to Frl by 8.5 cM, and the other marker C2_At4g28660 was linked by 0.016 cM.…”
mentioning
confidence: 99%
“…We then used the published tomato reference genome sequence (Tomato Genome Consortium 2012) (GenBank: GCA_000188115.2 Solyc2.50) as a reference to map sequence reads from both resistant and susceptible parents, and as well as sequences from both bulks. We concentrated on chromosome 9 around the previously published markers that were claimed to be linked to Frl (Truong et al 2011; Mutlu et al 2015). Initially, 1.2 Mb region covering some of the previous markers was taken into account and some of the identified SNVs at the flanking regions were converted to CAPS marker and were then used to map the Frl locus.…”
Section: Resultsmentioning
confidence: 99%
“…Previous mapping exercises have placed Frl on the chromosome 9 closely linked to the Tm-2 2 gene (Vakalounakis et al 1997). Several groups have used different approaches to generate PCR-based markers including RAPD (Fazio et al 1999) and SCAR (Mutlu et al 2015) markers. However, to our knowledge, the use of these markers in breeding programmes has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation